2021
DOI: 10.36956/sms.v2i1.306
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Study Applied to the Overtopping Wave Energy Converter Device

Abstract: The present study aims to analyze the state of the art of scientific studies about the Overtopping device used to convert sea wave energy into electrical energy, by means the Bibliometric Methodology. The development of this study took place through the selection of articles from conference proceedings, as well as national and international journals. The Bibliometric methodology consists of a statistical tool that allows quantifying the measurement of production indexes. Using selected keywords, it was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…As a result, many scholars have conducted literature reviews on offshore construction. Paiva et al [30] analyzed the current state of scientific research on wave energy converters (WEC) through bibliometric methods. They found that Brazilian universities are leading in productivity, accounting for more than 36% of the scientific results on WEC.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many scholars have conducted literature reviews on offshore construction. Paiva et al [30] analyzed the current state of scientific research on wave energy converters (WEC) through bibliometric methods. They found that Brazilian universities are leading in productivity, accounting for more than 36% of the scientific results on WEC.…”
Section: Introductionmentioning
confidence: 99%